Genetic Configuration of Genomic Resistance Islands in Acinetobacter baumannii Clinical Isolates From Egypt - Hamed, Samira M.; Hussein, Amira F. A.; Al-Agamy, Mohamed H.; Radwan, Hesham H.; Zafer, Mai M. (Frontiers in Microbiology, 2022)
In Acinetobacter baumannii (A. baumannii), a wide repertoire of resistance genes is often carried within genomic resistance islands (RIs), particularly in high-risk global clones (GCs). As the first in Egypt, the current study aimed at exploring the diversity and genetic configuration of RIs in the clinical isolates of A. baumannii. For this purpose, draft genomes of 18 isolates were generated by Illumina sequencing. Disk diffusion susceptibility profiling revealed multidrug resistance (MDR) and extensive drug resistance (XDR) phenotypes in 27.7 and 72.2%, respectively. The highest susceptibility was noted for tigecycline (100.0%) followed by colistin (94.4%), for which an MIC50 of 0.25 μg/ml was recorded by the broth microdilution assay. Sequence typing (ST) showed that the majority of the isolates belonged to high-risk global clones (GC1, GC2, and GC9). A novel Oxford sequence type (ST2329) that also formed a novel clonal complex was submitted to the PubMLST database. A novel blaADC variant (blaADC−258) was also identified in strain M18 (ST85Pas/1089Oxf). In addition to a wide array of resistance determinants, whole-genome sequencing (WGS) disclosed at least nine configurations of genomic RIs distributed over 16/18 isolates. GC2 isolates accumulated the largest number of RIs (three RIs/isolate) followed by those that belong to GC1 (two RIs/isolate). In addition to Tn6022 (44.4%), the comM gene was interrupted by AbaR4 (5.5%) and three variants of A. baumanniigenomic resistance island 1(AbGRI)-type RIs (44.4%), including AbaR4b (16.6%) and two novel configurations of AbGRI1-like RIs (22.2%). Three of which (AbaR4, AbaR4b, and AbGRI1-like-2) carried blaOXA−23 within Tn2006. With less abundance (38.8%), IS26-bound RIs were detected exclusively in GC2 isolates. These included a short version of AbGRI2 (AbGRI2-15) carrying the genes blaTEM−1 and aphA1 and two variants of AbGRI3 RIs carrying up to seven resistance genes [mphE-msrE-armA-sul1-aadA1-catB8-aacA4]. Confined to GC1 (22.2%), sulfonamide resistance was acquired by an ISAba1 bracketed GIsul2 RI. An additional RI (RI-PER-7) was also identified on a plasmid carried by strain M03. Among others, RI-PER-7 carried the resistance genes armA and blaPER−7. Here, we provided a closer view of the diversity and genetic organization of RIs carried by a previously unexplored population of A. baumannii.